Analisis Faktor-Faktor yang Mempengaruhi Indeks Pembangunan Manusia Di Indonesia Tahun 2023 - Syaidatussalihah, Syaidatussalihah; Mala, Faiqotul; Permata, Reny Amalia; Khalil, Adawiyah Asti (JSN : Jurnal Sains Natural, 2025)
The Human Development Index (HDI) is a composite indicator that reflects the quality of life of a population through three primary dimensions: health, education, and a decent standard of living. Improvements in HDI are supported by advancements across all its constituent factors. The dimension of long and healthy life is represented by the increase in life expectancy (LE), while the education dimension is captured through the rise in the mean years of schooling (MYS) and expected years of schooling (EYS). Additionally, the standard of living dimension is indicated by improvements in adjusted per capita expenditure. This study aims to analyze the factors that determine HDI in Indonesia in 2023 using multiple linear regression analysis. The data used in this study are secondary data sourced from the Central Statistics Agency in the form of Human Development Index data and the factors that influence it. The findings reveal that variables such as Life Expectancy (LE), Expected Years of Schooling (EYS), Mean Years of Schooling (MYS), and Adjusted Real Per Capita Expenditure significantly affect the Human Development Index in 2023. This is evidenced by an R-Square value of 0.9957, indicating that the independent variables collectively explain 99.57% of the variance in the dependent variable.